2012
DOI: 10.1063/1.4762816
|View full text |Cite
|
Sign up to set email alerts
|

Collective degrees of freedom involved in absorption and desorption of surfactant molecules in spherical non-ionic micelles

Abstract: Dynamics of absorption and desorption of a surfactant monomer into and out of a spherical non-ionic micelle is investigated by coarse-grained molecular dynamics (MD) simulations. It is shown that these processes involve a complex interplay between the micellar structure and the monomer configuration. A quantitative model for collective dynamics of these degrees of freedom is developed. This is accomplished by reconstructing a multi-dimensional free energy landscape of the surfactant-micelle system using constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Understanding how micellar dynamics and structure are connected to the chemical composition and geometry of the surfactants offers a considerable challenge. Numerous theoretical approaches and simulations have been proposed to predict structure–property relationships. Experimental techniques typically obtained by small-angle neutral scattering, static and dynamic light scattering, and cryogenic transmission electron microscopy, which can probe a wide range of length and time scales, are needed to fully characterize micelles and correlate the micellar structure to the dynamical behavior, a fundamental prerequisite for developing practical formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding how micellar dynamics and structure are connected to the chemical composition and geometry of the surfactants offers a considerable challenge. Numerous theoretical approaches and simulations have been proposed to predict structure–property relationships. Experimental techniques typically obtained by small-angle neutral scattering, static and dynamic light scattering, and cryogenic transmission electron microscopy, which can probe a wide range of length and time scales, are needed to fully characterize micelles and correlate the micellar structure to the dynamical behavior, a fundamental prerequisite for developing practical formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Martini simulations of micelles can also be used to provide starting structures for fine-grained models, as shown in a recent study on lyso-phospholipids, 266 and to provide details on the absorption and desorption process of non-ionic surfactants. 267 Bicelles, composed of double tail and single or short tail lipids, have also been the topic of a number of studies. 28,268,269 Carbohydrates Carbohydrates (saccharides) constitute a fundamental class of biomolecules and are present in a variety of emerging classes of biomimetic materials.…”
Section: Surfactant Self-assemblymentioning
confidence: 99%
“…MD simulation that describes the time dependent behavior of atomic/molecular systems is a widespread tool to explore the materials properties [43][44][45] and physical/chemical processes [46][47][48][49]. Despite of the limitation of its small time and length scales due to the A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 computational cost, it has been demonstrated that MD simulation can successfully carry out the investigations of atomic diffusivities [47][48][49].…”
Section: Simulation Detailsmentioning
confidence: 99%